ONCOGEN THERAPEUTICS INC. SPECIAL COMMITTEE OF THE BOARD OF DIRECTORS REPORT ON MAJOR INVESTIGATIVE TREADS (2023)
A 73% stock price drop in less than 3 months following a chronology of public statements questioned by the U.S. Food and Drug Administration, an ongoing FINRA investigation possibly referable to the Securities and Exchange Commission for potential insider trading concerns, and an employee whistleblower suggesting revealing non-privileged information regarding possible off-label marketing to the Department of Justice. OncoGen Therapeutics Inc. (“OncoGen”) is the epicenter of a delicate corporate situation which derives from the company’s approach to compliance as a side rather than a core business function. For 16 years, OncoGen developed its operation and became a billion-dollar revenue pharmaceutical multinational without a full-time Chief Compliance Officer. It is therefore a natural consequence that the company’s corporate risk assessment has been mostly reactive and not preventive, leading to the actual state of affairs. Furthermore, a detailed review of internal and governmental investigations exposes the Board of Directors (“BD”) and top executives’ actual knowledge and rationalization of continuous and repetitive red flags, towards which no significant and effective corrective action was taken. Nonetheless, taking a fundamental step to address these issues, OncoGen’s BD has conformed a Special Committee to oversee an internal investigation of the matters raised. Watson & Crick LLP (“W&C”) has been retained by the Special Committee to conduct a thorough examination and report the findings, reason why this document has been drafted. Specifically, the report focuses on detailing the relation between what happened and its explanation from a compliance -or lack of- perspective, who knew what was happening, what was being told to the public, and what was the action -or omission- in response. The report balances the likelihood that OncoGen sees itself involved in further governmental investigative procedures and private shareholder and investor litigation. The outcome of the analysis finds that the highest risk faced by the organization is due to the SEC’s and DOJ’s enforcement of the public company books and records provisions and false statements prohibition, given the apparent knowledge by the personnel with authority over public releases and consequent omission of material information. For possible insider trading concerns, it is probable that CFO Brigham will be involved in an insider trading investigation, with recent DOJ indictments suggesting a violation of insider trading prohibitions for cases with similar facts. For its part, a whistleblower involvement in the plausible off-label marketing of ZETARAL and uncertainty of the facts surrounding the case make it necessary for OncoGen to develop a thorough investigation as soon as possible to discover the full extent of the scheme and proceed with immediate remedial measures to avoid the whistleblower from coming forward. In the same vein, top level executives CEO and CFO are found to have had such high level of control, authority, and exercised sufficient discretion over the alleged unlawful activities that it is also clear that individual charges can be brought by the above-mentioned authorities. For its part, under Delaware standards, although the state offers strong protection against challenging discretion in business decisions, it is found that shareholders could validly assert action against the BD and executives seeking recovery for actual and eventual monetary damage to the company and themselves. W&C aims to raise awareness levels and explain the real danger faced by OncoGen for not approaching compliance as a fundamental axis of its operation. To that end, specific remedial measures are proposed that require elevating the compliance program to a level proportionate to the organization’s size and nature of its operations, and concrete advice is given on how to further develop the major investigative threads, assessing known and unknown corporate risks.